Data-driven medicine: The promise and potential of clinical decision support systems - Tariq, Saba; Tariq, Sundus (University of Faisalabad, 2024)
Patient safety is one of the most important factors involved in any health care policy. The idea of evidence-based medicine has emerged as the dominant paradigm in clinical practice, influencing our current understanding of medicine. Clinical decisions are based on accumulated scientific information in order to provide the best possible care, enhance patient outcomes, and save expenses.
Keywords: Clinical Decision Support Systems; Data-Driven Medicine; Physiology